2015
DOI: 10.15244/pjoes/36986
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Ethyl Acetate Extracts from Three Plant Materials (Shaddock Peel, Pomegranate Peel, Pomegranate Seed) and Their Algicidal Activities

Abstract: Eutrophication is a worldwide problem in aquatic ecosystems and cyanobacterial blooms can cause severe water quality deterioration due to toxin production, hypoxia, off-flavor problems that lead to illness in animals and humans [1][2][3]. Therefore, the removal of harmful cyanobacterial blooms is a crucial step for the maintenance of safe water supplies and for the safety of aquatic products [4]. Recent years have seen many studies relating to the isolation and identification of allelochemicals from aquatic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Among the solvents used, ethyl acetate, methanol, and acetone seem to be the best for extracting antioxidants, as demonstrated by the results of the DPPH assay (Table ), and other assays, in which the peel extracts prepared with ethyl acetate and methanol, reached significantly ( P < 0.05) better results that the ones with pulps. These results obtained for C. maxima are in agreement with the ones from different species of Citrus (Jayaprakasha et al, ; Klangpetch et al, ; Wang et al, ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Among the solvents used, ethyl acetate, methanol, and acetone seem to be the best for extracting antioxidants, as demonstrated by the results of the DPPH assay (Table ), and other assays, in which the peel extracts prepared with ethyl acetate and methanol, reached significantly ( P < 0.05) better results that the ones with pulps. These results obtained for C. maxima are in agreement with the ones from different species of Citrus (Jayaprakasha et al, ; Klangpetch et al, ; Wang et al, ).…”
Section: Resultssupporting
confidence: 90%
“…For instance, Klangpetch et al () found that the ethyl acetate peel extract of kaffir lime possesses high levels polyphenols and also antioxidant and antimicrobial potential and then investigated it in prolonging the shelf life of raw chicken drumettes. As Wang et al () identified allelochemicals with algicidal activity from the ethyl acetate extracts of Citrus peel, including shaddock peel. Benavente‐Garcia et al () reviewing about flavonoids, mentioned that several biological properties such as anticarcinogenic, cardiovascular, and antimicrobial of these substances are related to their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With their main composition of lignocellulose, terpene, phenolic, nootkatone, etc. [24], the ISSs could be converted into chars during the simultaneous carbonization-activation process at 900°C. Synchronously, a rapid contraction…”
Section: Gcns Fabricationmentioning
confidence: 99%
“…Numerous studies have reported the inhibition of cyanobacterial biomasses by several aquatic plants such as Potamogeton maackianus (Wu et al, 2007), Myriophyllum spicatum (Zhu et al, 2010), Sagittariatrifolia (Li et al, 2016), and Eichhornia crassipes (Zhou et al, 2014). To explore the potential of terrestrial plant extracts for controlling cyanobacteria provide a new guide for developing algicide (Shao et al, 2013 (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%